Meal timing variability of rotating shift workers throughout a complete shift cycle and its effect on daily energy and macronutrient intake: a field study. - Pereira Marot, Luisa; Tibiletti Balieiro, Laura Cristina; do Vale Cardoso Lopes, Tássia; Rosa, Dayane Eusenia; Wright Jr, Kenneth P.; de Castro Moreno, Claudia Roberta; Crispim, Cibele Aparecida (European Journal of Nutrition, 2023)
Purpose: To evaluate the meal timing variability of rotating shift workers throughout a complete shift schedule and its effect on daily energy and macronutrient intake. Methods: Thirty male shift-workers from a mining company were evaluated in a complete rotation shift cycle over 240 consecutive hours (10 days; two days of morning shifts, two days of evening shifts, 24 h free, two days of night shifts and three days off). Food intake related variables [meal timing, energy (kcal) and macronutrient intake (%)] were assessed by 24 h recall by a trained nutritionist. Mixed models were used to analyze the variation in meal timing and energy and macronutrient intake throughout the shift cycle, as well as the interaction between shift and time ranges (00:00–03:59, 04:00–07:59, 08:00–11:59, 12:00–15:59, 16:00–19:59, 20:00–23:59). Results: The first meal of the day was earlier on night shifts [D6 (3:44 ± 0:33) and D7 (5:52 ± 0:42)] compared to the other shifts (p < 0.001), except for D4 (evening shift; 5:51 ± 0:47) versus D7 (p = 0.999). Night shifts also showed a shorter night fasting (D5–D6, 9.3 h; D6–D7, 9.6 h) than most other nights (p < 0.05), except for the fasting between D1–D2 (11.3 h) and D3–D4 (11.2 h) (p > 0.05). There was no difference in 24 h energy intake throughout the shift cycle (p = 0.065). The analysis of interaction between shift and time ranges showed that night shift (D6) presented a higher intake of energy (441.5 ± 48.4 kcal), percentage of energy (D6: 17.8 ± 1.8%), fat (17.6 ± 2.0%), carbohydrate (17.0 ± 1.7%) and protein (16.4 ± 1.8%) between 00:00 and 03:59 compared with the other shift days (p < 0.05). Conclusion: Night shifts seem to contribute to a longer eating window than other shifts. Moreover, there is a higher energy and macronutrients intake during night shifts, which reduces the night fast period and could have implications for metabolic dysregulation.